2008
DOI: 10.1186/1471-2164-9-64
|View full text |Cite
|
Sign up to set email alerts
|

Up regulation in gene expression of chromatin remodelling factors in cervical intraepithelial neoplasia

Abstract: Background: The highest rates of cervical cancer are found in developing countries. Frontline monitoring has reduced these rates in developed countries and present day screening programs primarily identify precancerous lesions termed cervical intraepithelial neoplasias (CIN). CIN lesions described as mild dysplasia (CIN I) are likely to spontaneously regress while CIN III lesions (severe dysplasia) are likely to progress if untreated. Thoughtful consideration of gene expression changes paralleling the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
2
19
0
2
Order By: Relevance
“…It is also thought to contribute to tumorigenesis and tumor progression (38). Interestingly, two very recent studies have shown that BAF155 is highly expressed in malignant and neoplastic areas (47,48). These observations correlate with our findings that SWI/SNF induces HIF-1␣ expression.…”
Section: Figure 7 Baf57 Is Required For Hypoxia-induced Arrest In Prsupporting
confidence: 91%
“…It is also thought to contribute to tumorigenesis and tumor progression (38). Interestingly, two very recent studies have shown that BAF155 is highly expressed in malignant and neoplastic areas (47,48). These observations correlate with our findings that SWI/SNF induces HIF-1␣ expression.…”
Section: Figure 7 Baf57 Is Required For Hypoxia-induced Arrest In Prsupporting
confidence: 91%
“…Instead of BAF155 loss, BAF155 overexpression can also be seen. Gene expression analysis of cervical intraepithelial neoplasias (CIN) and normal cervical tissue shows elevated BAF155 in CIN III lesions, which are the most dysplastic [ 69 ]. Similarly, in prostate cancer, elevated BAF155 by IHC is correlated with increased Gleason score ( p < 0.05), increased stage ( p < 0.01), and decreased time to recurrence ( p = <0.001).…”
Section: Baf155/baf170 and Tumorigenesismentioning
confidence: 86%
“…7,8 All specimens were collected by bite biopsy under colposcopic guidance targeting a small portion of the affected epithelium immediately before the loop electrosurgical excision procedure and were stored at j80-C in RNAlater (Ambion) within 2 minutes of retrieval. The excised loop electrosurgical excision procedure tissues were fixed with formalin paraffin embedded, cut, and hematoxylin and eosin stained.…”
Section: Clinical Specimensmentioning
confidence: 99%
“…7,8 Four L-SAGE libraries were constructed from nonneoplastic untyped cervical tissue, three from mild dysplasia (CIN1) samples, three from moderate dysplasia (CIN2) samples, and six from severe dysplasia (CIN3) samples (Table 1). Briefly, biopsies were homogenized in lysis binding buffer (100-mmol/L Tris-HCl, pH7.5; 500-mmol/L LiCl; 10-mmol/L EDTA, pH 8.0; 1% LiDS; 5-mmol/L dithiothreitol), and libraries constructed using the L-SAGE kit (Invitrogen, Ontario, Canada) and sequenced to an average depth of 155,000 tags.…”
Section: L-sagementioning
confidence: 99%